Object-wave reconstruction by carbon film-based Zernike- and Hilbert-phase plate microscopy: A theoretical study not restricted to weak-phase objects - Dries, Manuel Rainer; Schultheiss, K.; Gamm, B.; Rosenauer, A.; Schröder, Rasmus R.; Gerthsen, D. (Ultramicroscopy, 2011)
Transmission electron microscopy phase-contrast images taken by amorphous carbon film-based phase plates are affected by the scattering of electrons within the carbon film causing a modification of the image-wave function. Moreover, image artefacts are produced by non-centrosymmetric phase plate designs such as the Hilbert-phase plate. Various methods are presented to correct phase-contrast images with respect to the scattering of electrons and image artefacts induced by phase plates. The proposed techniques are not restricted to weak-phase objects and linear image formation. Phase-contrast images corrected by the presented methods correspond to those taken by an ideal centrosymmetric, matter-free phase plate and are suitable for object-wave reconstruction.
Available online 20 October 2010
Gesehen am 30.03.2022